Exercise and adiposity in overweight and obese children and adolescents: protocol for a systematic review and network meta-analysis of randomised trials - Kelley, George A (BMJ Open, 2017)
INTRODUCTION: Overweight and obesity is a worldwide public health problem among children and adolescents. However, the magnitude of effect, as well as hierarchy of exercise interventions (aerobic, strength training or both), on selected measures of adiposity is not well established despite numerous trials on this issue. The primary purposes of this study are to use the network meta-analytical approach to determine the effects and hierarchy of exercise interventions on selected measures of adiposity in overweight and obese children and adolescents. METHODS AND ANALYSIS: Randomised exercise intervention trials >4 weeks, available in any language up to 31 August 2017 and which include direct and/or indirect evidence, will be included. Studies will be located by searching seven electronic databases, cross-referencing and expert review. Dual selection and abstraction of data will occur. The primary outcomes will be changes in body mass index (in kg/m(2)), fat mass and percent body fat. Risk of bias will be assessed using the Cochrane Risk of Bias assessment instrument while confidence in the cumulative evidence will be assessed using the Grading of Recommendations Assessment, Development and Evaluation instrument for network meta-analysis. Network meta-analysis will be performed using multivariate random-effects meta-regression models. The surface under the cumulative ranking curve will be used to provide a hierarchy of exercise treatments (aerobic, strength or both). ETHICS AND DISSEMINATION: This study does not require ethics approval. Findings will be presented at a professional conference and published in a peer-reviewed journal. PROSPERO REGISTRATION NUMBER: CRD42017073103.